2010
DOI: 10.2172/990105
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Heat Transfer with Pool and Spray Impingement Boiling on Microporous and Nanowire Surface Coatings

Abstract: The National Renewable Energy Laboratory (NREL) is leading a national effort to develop next-generation cooling technologies for hybrid vehicle electronics, as part of the Advanced Power Electronics and Electrical Machines program area in the U.S. Department of Energy's (DOE's) Vehicle Technologies Program. The overarching goal is to reduce the size, weight, and cost of power electronic modules that convert direct current from the batteries to alternating current for the motor, and vice versa. Aggressive therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…This non-monotonic behavior of wetting and wicking in turn leads to significant decrease of CHF. This trend was also observed by previous studies using nanowire-coated boiling surfaces on highly-wetting dielectric fluids [20,21]. It may be attributed to coupled interactions between capillary flow and liquid entrainment, which lead to a flow regime transition from the annular flow into a wispy-annular flow or a churn flow.…”
Section: Introductionsupporting
confidence: 84%
“…This non-monotonic behavior of wetting and wicking in turn leads to significant decrease of CHF. This trend was also observed by previous studies using nanowire-coated boiling surfaces on highly-wetting dielectric fluids [20,21]. It may be attributed to coupled interactions between capillary flow and liquid entrainment, which lead to a flow regime transition from the annular flow into a wispy-annular flow or a churn flow.…”
Section: Introductionsupporting
confidence: 84%
“…Kim et al [10] studied the mechanism of pool boiling with FC-72 on cylindrical platinum wire with a diameter of 390 lm using high-speed photography. The 17-lm-thick coating was made from dielectric DOM (8)(9)(10)(11)(12) lm synthetic diamond particles/OMEGABOND 101 epoxy binder/methyl-ethyl-ketone carrier). They found that the diameter at departure of bubbles on the microporous surface was lower than the plain surface.…”
Section: Introductionmentioning
confidence: 99%
“…At high heat fluxes, convection heat transfer became larger than latent heat, possibly due to the decrease in the superheated liquid layer at the surface, which inhibits latent heat transfer. Thiagarajan et al [11,12] studied pool boiling and spray impingement boiling on a vertically oriented 10-mm  10-mm copper surface coated with a 100-lm-thick microporous layer (similar to the one used in the current work). They found that the pool boiling heat transfer coefficient was enhanced by 500% on the microporous surface compared to the plain surface [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially true at micro-and nano-scale dimensions, where interactions at liquid interfaces can have a dramatic influence on the macroscopic properties of the system, dictating physical properties like the fluid viscosity, thermal conductivity, and surface tension. Over the past several years, several groups have shown that micro-and nanostructures can enhance the overall heat transfer coefficient in pool boiling [3][4][5], flow boiling [6,7], spray cooling [8][9][10], heat pipes, and post-CHF film boiling [11]. Nanowire-like structures have also been predicted to enhance the long-range van der Waals interactions at solid interfaces [12,13], which, in turn, dictate the formation of specific liquid-wetting [14] and gas-spreading [15] states at a liquid-solid interface.…”
Section: Introductionmentioning
confidence: 99%